2020
DOI: 10.3390/antibiotics9110830
|View full text |Cite
|
Sign up to set email alerts
|

African Plant-Based Natural Products with Antivirulence Activities to the Rescue of Antibiotics

Abstract: The worldwide emergence of antibiotic-resistant bacteria and the thread of widespread superbug infections have led researchers to constantly look for novel effective antimicrobial agents. Within the past two decades, there has been an increase in studies attempting to discover molecules with innovative properties against pathogenic bacteria, notably by disrupting mechanisms of bacterial virulence and/or biofilm formation which are both regulated by the cell-to-cell communication mechanism called ‘quorum sensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 83 publications
0
16
0
Order By: Relevance
“…Absorbance was measured at 280 nm using the UV-vis technique (U-2900 spectrophotometer, Hitachi High-Technologies Corporation, Tokyo, Japan). Several measurements were performed for each sample, and the cumulative drug release of PCA from nanoformulations was calculated based on the following Equations ( 1) and (2): % of mass released at time t = (mass (t)/total mass of the drug in the nanoformulation) × 100 (1) cumulative % = mass (t − 1) + mass (t) for the current measurement (2) where mass (t) is the percentage release at the time of measurement and t − 1 is the percentage of the released drug at the previous timepoint. For kinetic model fitting, we analyzed the data for release profiles using pharmacokinetics software (KinetDS3, developed at Jagiellonian University, Krakow, at the Faculty of Pharmacy's Department of Pharmaceutical Technology and Biopharmaceutics).…”
Section: In Vitro Releasementioning
confidence: 99%
See 1 more Smart Citation
“…Absorbance was measured at 280 nm using the UV-vis technique (U-2900 spectrophotometer, Hitachi High-Technologies Corporation, Tokyo, Japan). Several measurements were performed for each sample, and the cumulative drug release of PCA from nanoformulations was calculated based on the following Equations ( 1) and (2): % of mass released at time t = (mass (t)/total mass of the drug in the nanoformulation) × 100 (1) cumulative % = mass (t − 1) + mass (t) for the current measurement (2) where mass (t) is the percentage release at the time of measurement and t − 1 is the percentage of the released drug at the previous timepoint. For kinetic model fitting, we analyzed the data for release profiles using pharmacokinetics software (KinetDS3, developed at Jagiellonian University, Krakow, at the Faculty of Pharmacy's Department of Pharmaceutical Technology and Biopharmaceutics).…”
Section: In Vitro Releasementioning
confidence: 99%
“…As microorganisms exhibit an increasing and troubling resistance to drug therapies, including antibiotics, the search for new solutions has become urgent. The growing prevalence of resistant bacteria poses a global public health threat [ 1 ] as pathogens become adapted to the most frequently used antibiotics [ 2 ]. Novel strategies are needed, especially those that rely on alternative drug sources, including natural agents from plant-derived compounds [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This issue has forced researchers to constantly search for novel effective antimicrobial agents against different pathogenic bacteria. These antimicrobial agents could work via disrupting bacterial virulence such as biofilm formation [18]. Bacterial pathogenicity is defined as its ability to cause disease.…”
Section: Introductionmentioning
confidence: 99%
“…Suggesting that it is possible it has more than one molecular target. The wide variety of viral targets of EHX possibly showed its broad diverse antiviral activities, as plant-based natural products are considered as reservoir and prolific source of chemicals with a very broad spectrum of biological activities ( Pham et al, 2019 ; Mahavy et al, 2020 ). Furthermore, a study showed that plant-derived volatile compounds have short half-life and can be rapidly catabolized and degraded ( Oikawa and Lerdau, 2013 ).…”
Section: Discussionmentioning
confidence: 99%